Funding Constraints and Market Illiquidity in the European Treasury Bond Market - Sophie Moinas; Minh Nguyen; Giorgio Valente (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2018)
Theoretical studies show that shocks to funding constraints should affect and be affected by market illiquidity. However, little is known about the empirical magnitude of such responses because of the intrinsic endogeneity of illiquidity shocks. This paper adopts an identification technique based on the heteroskedasticity of illiquidity proxies to infer the reaction of one measure to shocks affecting the other. Using data for the European Treasury bond market, we find evidence that funding illiquidity shocks affect bond market illiquidity and of a weaker, but significant, reverse feedback effect. We also find that, in the cross-section, the responses of individual bonds' market illiquidity to funding illiquidity shocks increase with bond duration, the credit risk of the issuer, and with haircuts.
Keywords: 330